UKRAINIAN THEATRICAL PROJECTS AS AN EXAMPLE OF ANTHROPOLOGICAL DEFENSE IN TERMS OF ANTHROPOLOGY AS CONTEMPORARY SOCIAL WARFARE - Korzeniowska-Bihun, A.; Boroch, R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Anthropological aggression is a means of waging war using information gained from a nation and its culture, social norms and habits and geographic conditions, as well as its history, traditions, etc. This type of activity is currently observed in Ukraine in the context of the war in the eastern part of the country. Anthropological aggression, however, can be minimized by the use of the anthropological defence. An example of this is the theatrical projects initiated by various artistic troupes all over the country. This paper presents the methods which are employed by the Ukrainian theatre to counteract this anthropological aggression. One can identify four basic fields of activity directed at creating the tools of anthropological defence: 1) combating stereotypes; 2) facilitating the integration and assimilation of internally displaced people; 3) theatrotherapy: 4) initiation of the social and political debate.